Experimental Study of the Physical and Mechanical Properties of Cement-Based Composite Reinforced With Macro-/Microfibers: Case of Rhecktophyllum camerunense and Triumfetta pentandra - Azemafac Desmond Nkapleweh; Josepha Foba Tendo; Fabien Betene Ebanda; Tido Tiwa Stanislas; Yakum Reneta Nafu; Armel Edwige Mewoli (Advances in Civil Engineering)
Plant fibers have the ability to bridge crack propagation on a microscopic scale for microfibers and on a macroscopic scale for macrofibers. Therefore, the use of two or more fiber types in an appropriate combination can potentially improve the overall properties of the cement composite as well as promote green construction. The hybrid composite was cast using random orientation with two fibers: Rhecktophyllum camerunense as macrofiber and Triumfetta pentandra as microfiber. Cement mortar matrices were reinforced with a constant microfiber length of 1 mm and three different macrofiber lengths of 1.5, 3, and 6 mm at varying fiber contents of 1%, 1.5%, and 2.5% wt. The physical characteristics of the composite were assessed by porosity, density, and water absorption. Mechanically, three-point bending tests and single-edge notch bending (SENB) tests were performed after 7 and 14 days of curing. Mode I fracture behavior (KIC) and modulus of rupture (MOR) were calculated as per formulation. Physical experimental results reveal that there is a correlation between the rate of water absorption, porosity, density, and that of the fiber loading and length in the composite. Mechanically, the developed material presented a multiple cracking behavior under bending. There was a decrease in MOR and fracture toughness values with a decrease in macrofiber content in the hybrid composite. They both presented an increase in value with an increase in fiber content and fiber length. The composites reinforced with both fibers presented higher values of MOR than the unreinforced due to the powerful interfacial bond between the fibers and the cement matrix. The unreinforced composites had the least MOR and fracture toughness values of 0.442 MPa and 694,000 N.m1.5, respectively, showing that they are very reactive to faults at low stress levels.